2023
DOI: 10.1167/tvst.12.1.19
|View full text |Cite
|
Sign up to set email alerts
|

RANTES (CCL5) in Patients With Geographic Atrophy Age-Related Macular Degeneration

Abstract: Purpose A previous study from our research group showed significantly lower levels of RANTES (Regulated upon Activation, Normal T Cell Expressed and Secreted) in patients with intermediate age-related macular degeneration (AMD) compared to control patients with no AMD. The primary aim of this study was to assess levels of RANTES in a cohort of patients with a more advanced form of the disease, geographic atrophy (GA), in comparison with controls. Methods The study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The inclusion and exclusion criteria and informed consent are described in detail elsewhere. 18 , 19 , 22 In summary, inclusion criteria for case subjects included in the registry are aged between 55 and 99 years, unilateral or bilateral AMD, and capacity for informed consent. Exclusion criteria include: branch and central retinal vein occlusion with severe macular damage, pan-retinal photocoagulation or anti-VEGF injections for diabetic retinopathy, active ocular inflammatory disease, treatment with select immunosuppressives, serious mental health or terminal illnesses, and a decrease in visual acuity secondary to a severe pre-existing retinal disease except AMD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion and exclusion criteria and informed consent are described in detail elsewhere. 18 , 19 , 22 In summary, inclusion criteria for case subjects included in the registry are aged between 55 and 99 years, unilateral or bilateral AMD, and capacity for informed consent. Exclusion criteria include: branch and central retinal vein occlusion with severe macular damage, pan-retinal photocoagulation or anti-VEGF injections for diabetic retinopathy, active ocular inflammatory disease, treatment with select immunosuppressives, serious mental health or terminal illnesses, and a decrease in visual acuity secondary to a severe pre-existing retinal disease except AMD.…”
Section: Methodsmentioning
confidence: 99%
“… 14 16 The overarching hypothesis for our research is that systemic inflammation contributes to local ocular events in AMD and identification of systemic biomarkers may lead to earlier diagnosis and targeted therapies to prevent further visual damage. In research to date, we have demonstrated a significant role for systemic inflammatory markers, specifically cytokines, 14 , 16 chemokines, 17 19 and complement factors, 20 22 with sex-specific modulation of the complement system 22 and RANTES 18 , 19 in AMD.…”
Section: Introductionmentioning
confidence: 99%